Front Matter (Journal of the Assembly for Expanded Perspectives on Learning, 2004)
Editors' Message At Risk: Teaching and Writing Outside the Safety Zone In 1983, the National Commission on Excellence in Education released its damning indictment of American education. In the opening sentence of the report, the authors announce: "Our Nation is at risk." National prosperity, security, and civility are being "eroded by a rising tide of mediocrity" resulting from the failures of our schools and colleges. Within this context "risk," defined by Webster's as "the possibility of suffering loss," is something to be avoided, or, if that is not possible, something to be managed. Thus, children struggling for success in school for whatever reason are categorized "at risk"; readers and writers who come to the classroom with an array of language habits divergent from those practiced in the middle-class circles are placed in "at risk" programs. The urge is to mitigate risk, to reduce the possibility of any loss of prosperity, security, and civility. Every afternoon during my sixth grade year, between 2:15 and 2:45, I strapped on my cross belt decorated with my badge of authority, loaded up my flag, and joined the Safety Patrol. With my partner, Bobbi Jo Lee, I stood at the curb on Jenny Street, a lazy two-lane side street, outside the double doors of Neff Elementary School, protecting the younger students as they walked home. After crossing our flags to herd the students at the curb, Bobbi Jo and I would step into the street, stand precisely on the parallel white lines marching across Jenny Street, and stop traffic. With our bodies, our flags, and our badges, Bobbi Jo and I created a safety zone—a risk free zone—for noisy, exuberant children to dance from one side of Jenny Street to the other. At the end of the year, I reluctantly turned in my cross belt and my flag. now, years later, I wonder if I have carried that flag and badge with me, extending parallel white lines until I live and teach only within that safety zone. As well as the possibility of suffering loss, risk also carries with it a sense of the possibility of great gain. For instance, Gregory Bateson tells us that no learning occurs without an element of risk, for the learner must experience the rain of the random. We cannot grow, transform, or blossom without undergoing the threat of chaos because new order evolves out of chaos. Therefore, risk is an opportunity, one we should court. By avoiding risk—by correcting it, fighting it, or managing it—we erode opportunities to learn. During the summer of 1965, my friends and I, thumbs outstretched, would stand at the entrance to the Belt Parkway on Fourth Avenue and Sixty-fifth Street waiting for some passing motorist to slow down and offer us a ride. We'd usually have two or three girls out front, and, when a car would stop, a couple of the boys would come forward. We'd work to convince drivers that we were safe kids, good kids, no problem at all. If they'd take a girl and two boys, we had truly lucked out. More often, they'd leave us flat or maybe take two girls with one boy. This is how we got to Riis Park Beach when I was an eighth grader. There wasn't a subway to get there, and the buses just took too long. If we drew a total blank, we'd take the subway to Brighton Beach, but that was our last resort. We wanted the clean beach with the rough waves: Riis Park was our spot. Standing at the entrance to the highway, keeping out a weather eye for wild drivers, we judged the rewards well worth the risks. The importance and positive value of risk is the unifying theme of our tenth volume of JAEPL, At Risk: Teaching and Writing outside the Safety Zone. More specifically, the essays in this issue focus on the necessity of risk in teaching and writing, for without that risk we cannot teach; we merely replicate conventional and many times limited ways of knowing. If we protect ourselves, if we teach only within a narrow safety zone, we cannot invite our students to invest in their learning, to risk who they are and what they know. Instead, we must step outside of that safety zone. The essays in this issue trail blaze that risky path for us by offering myriad perspectives on and examples of risk taking in teaching and writing. Lynn Z. Bloom in The Seven Deadly Virtues enacts that risk and urges us to do the same. In a personal record of her journey as a writer, Bloom highlights the importance of risking ourselves in and through our writing. She points to the seven deadly virtues of "good" writers, safe writers—duty, rationality, conformity, conventionality, efficiency, economy, and order—and suggests instead the importance to writers of the lively sins of innovation: a "risky, messy, passionate, and uncertain process, accommodating the disorder and inefficiency of randomness and the necessary time out for reflection and revision. In Shallow Literacy, Timid Teaching, and Cultural Impotence, David L. Wallace shifts the site of risk to the classroom, arguing for the kind of pedagogy that involves "both personal and professional risk." Recounting a moment in his teaching in which he shared an intensely personal narrative, Wallace argues for the necessity of such risks if we wish to challenge the dominant view of literacy that continues to marginalize too many of our students and imprison our thinking. Roben Torosyan in Listening: Beyond Telling to Being What We Want To Teach offers readers a strategy for trust-building—group empathy—that helps students develop multifaceted perspectives and tolerance. However, this strategy is most effective, Torosyan explains, when teachers take the risk of self-disclosing, of discussing mistakes, missteps, and misconceptions. Teachers have to "actually embody or 'be' precisely the kind of self-examining listeners: that they want their students to become. Without such risk, no trust building is possible. This "confessional consciousness," while sometimes painful, models the kind of thinking that students need for life-long learning. As Torosyan points out, "the more I dare to slip up. . . the more they gain the courage to do likewise." Changing the venue and the arena of risk, Patricia Webb and Zach Waggoner in Analyzing the Dominant Cultural Narratives of Religious Pluralism: A Study of Oprah.com, reveal the threat to spiritual pluralism in the age of the Internet through a meticulous analysis of the shifts in Oprah Winfrey's website, from the 2002 to the 2004 website design. The authors argue that Oprah.com morphed from a daring, unconventional venue for religious pluralism in 2002 to a far more conservative and narrowly construed venue advocating an implicit traditional Christian orientation in 2004. The early website took necessary risks, creating opportunities for the growth of religious pluralism. Without such risk taking, however, the more conservative 2004 website undermines that pluralism, restricting spirituality to a single, narrow perspective. Matthew I. Feinberg in Critical Geography and the Real World in First Year Writing Classrooms explores the risky connection between mind and body, mind and place. "We are bodies that teach and learn in physical spaces," he reminds us, and without a more direct acknowledgement of that, "the work of the classroom will continue to be the fiction within the lives of our students." He advocates an approach to teaching that requires teacher and student to grapple with the "spatial and tangible components of ideology and culture" by studying the varied physical environments within which students live and learn. By taking this risk, by turning around on our taken-for-granted ontological realities, we hold the hope of moving university classroom and real world into a closer embodied alignment. Hildy Miller in Image into Word: Glimpses of Mental Images in Writers Writing shifts us from the outer world of Feinberg's critical geography to the inner world of students' mental imagery. Contesting traditional language centered approaches to writing and researching writing, Miller asks what role imagery might play in the composing of her students. She explores that question by collecting from her students "though sample" questionnaires as they produced text, deducing from these questionnaires and the students' essays the presence and function of mental imagery in expository writing. Results of this study suggest the need to risk our accepted pedagogical and assessment practices so that we might better honor the "pervasiveness and importance" of mental imagery in writing. Finally, Ed Comber in Critical Thinking Skills and Emotional-Response Discourse: Merging the Affective and Cognitive in Student-Authored Texts through Taxonomy Usage describes a strategy that helps students identify discourse markers that indicate the presence of interfering emotions. Rather that eradicate emotion, teachers need to risk focusing students' attention directly on what Comber calls their "emotive-response discourse," a move that enables students to work through those emotions. Andrew Marvell in To My Coy Mistress, that amusing turn on seduction, urges his recalcitrant mistress to defy convention, to cease to play it safe and preserve a virtue that ultimately will be defiled by worms. Rather, with time rushing them to death, he urges her to risk everything: Let us roll all our strength and all Our sweetness up into one ball, And tear our pleasures with rough strife Thorough the iron gates of life: To savor life, the two need to stop playing it safe. They need to take a risk. The essays in this volume of JAEPL show us ways that we, too, can roll up our strength and sweetness to make and seize opportunities in our teaching and our writing. "Let's do something a little different with Richards," I announce abruptly with a flutter beneath my breastbone. The nine faces of my graduate students turn to me warily. For the last long painful 40 minutes, we have been trying to discuss I. A. Richards's Philosophy of Rhetoric. It is not pretty. Desperately searching for the "right" answer, my students are afraid to risk any answer. "I want you to draw me a map, a treasure map, the kind that we used to create in second grade, or, at least, the kind that I created. The treasure map in this map is Richards's idea of metaphor. That's where X marks the spot. So how do we get there? Start with context and figure out where Proper Meaning Superstition, Club Spirit, and other obstacles get between you and the treasure." It was a risky move for them and for me, putting all of us outside the safety zone, beyond flags, well on our way, thumb in the air, to Riis Park Beach. Works Cited Bateson, Gregory. Mind and Nature: A Necessary Unity. New York: E. P. Dutton, 1979. Marvell, Andrew. To His Coy Mistress. The Oxford Book of English Verse: 1250-1900. Ed. Arthur Quiller-Couch. Oxford: Oxford UP, 1919. 12 July 2004 http://www.bartleby.com/101/357.html . United States. Dept. of Education. A Nation At Risk: An Imperative for Educational Reform. April 1983. National Commission on Excellence in Education. 15 August 2004 http://www.ed.gov/pubs/NatAtRisk/index.html .